Metal‐Free‐Mediated Oxidation Aromatization of 1, 4‐Dihydropyridines to Pyridines Using Visible Light and Air. Issue 12 (3rd November 2014) - Wei, Xiaojing; Wang, Lin; Jia, Wenliang; Du, Shaofu; Wu, Lizhu; Liu, Qiang
Abstract A metal‐free and environmentally friendly aerobic aromatization photosensitized by organic dye eosin Y bis(tetrabutyl ammonium salt) (TBA‐eosinY) has been developed. With the aid of K2CO3, the aerobic catalytic system converts 1, 4‐dihydropyridines to their corresponding pyridine derivatives efficiently under visible light irradiation (λ=450 nm) at room temperature.